2010
DOI: 10.1016/j.pscychresns.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Depression severity is correlated to the integrity of white matter fiber tracts in late-onset major depression

Abstract: Cerebral white matter lesions (WMLs) are believed to play an important role in a subset of major depression (MD). We aimed to describe the impact of WMLs on white matter pathways in MD using diffusion tensor imaging (DTI) and magnetization transfer imaging. As a novel approach, we used DTI tractography to assess pathways intersected by WMLs. We examined 22 patients with late-onset MD and 22 age-and gendermatched controls. Parametric maps of fractional anisotropy (FA), apparent diffusion coefficient (ADC), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
82
4
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 107 publications
6
82
4
1
Order By: Relevance
“…The results of meta-regression analysis showed that there was no significant association between white matter microstructure alterations and relevant socio demographic and clinical variables. The results, however, should be interpreted with some caution in consideration of the small sample size in the present study and the limited variability in the data, since some studies investigating white matter abnormalities in patients with MDD have provided evidence that decreased FA in the SLF and CC were associated with the depressive symptoms 14,39,44,[64][65][66] and negatively cor related with depression severity 28,65,67,68 and illness duration. 14,28 Moreover, patient characteristics of the included studies were heterogeneous, which may result in the negative results.…”
Section: Discussionmentioning
confidence: 76%
“…The results of meta-regression analysis showed that there was no significant association between white matter microstructure alterations and relevant socio demographic and clinical variables. The results, however, should be interpreted with some caution in consideration of the small sample size in the present study and the limited variability in the data, since some studies investigating white matter abnormalities in patients with MDD have provided evidence that decreased FA in the SLF and CC were associated with the depressive symptoms 14,39,44,[64][65][66] and negatively cor related with depression severity 28,65,67,68 and illness duration. 14,28 Moreover, patient characteristics of the included studies were heterogeneous, which may result in the negative results.…”
Section: Discussionmentioning
confidence: 76%
“…The orbitofrontal cortex is part of the medial prefrontal network and is considered essential for reward-based decision-making; it is known to be dysfunctional in affective disorders (25). There have been demonstrations of associations between severity of depressive symptoms and WM integrity in the right uncinate fasciculus in depressive patients and in patients with a history of brain concussion (6,8,28,36), but this is the first report of a correlation between affective symptoms and FA in the right uncinate fasciculus in brain tumor patients. We used an ROI approach to analysis of FA scores in data acquired with a 1.5 Tesla MRI system.…”
Section: Discussionmentioning
confidence: 78%
“…DTI is widely used in psychiatric neuroscience to reveal abnormal connectivity between core brain regions of neural networks linked to affective symptoms (10,14,37). Changes of the FA in different brain regions have been shown to be related to the severity of depressive symptoms (5,8,23).…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact function of the UF in MDD is not well understood, a recent study of late-onset major depression found that depression severity significantly correlated with lower FA in white matter lesions of the right UF (Dalby et al, 2010). In contrast, Taylor et al (2007) found early-onset geriatric depressed subjects exhibited lower FA of the left UF compared with mid and late onset or HC subjects.…”
Section: Discussionmentioning
confidence: 98%